Consensus or Conflict?: a Survey Analysis of How Norwegians Interpret the July 22, 2011 Attacks a Decade Later - Solheim, Øyvind Bugge (Perspectives on terrorism, 2021)
The dominant narrative about the right-wing terrorist attacks in Norway on July 22, 2011, suggests that they were an attack on the Norwegian democracy, that the perpetrator was motivated by right-wing extremism and that Norway reacted by emphasizing tolerance, democratic values, and inclusion. Surveys carried out in the aftermath of the attacks show that this narrative received widespread support. In this article, we use a nationally representative survey to analyze how Norwegians interpret the July 22 attacks today - a decade later. We find significant levels of consensus, but also traces of conflict. While there are high levels of agreement regarding many of the interpretive frames, some of the frames are more contested. Moreover, some of these contested interpretations are associated with three conflicting narratives about the terrorist attack: the democracy narrative, the diversity narrative and the far-right narrative. These narratives are all characterized by a distinct understanding of why the attacks happened, who was targeted and how society reacted to the attacks. Given that the support for the different narratives varies according to ideological beliefs, partisanship, levels of trust and, to some extent, emotional reactions, we argue that discussions about July 22 today are likely to be politically polarizing - or even irreconcilable. The article shows how terrorist attacks that appear uniting in the short run may become more divisive in the long run, mirroring other existing political conflicts in society.